2016
DOI: 10.1002/mar.20875
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Procedural Fairness in Electronic Reverse Auctions to Enhance Relationship Quality

Abstract: In this study, the use of procedural fairness by a buying organization in an electronic reverse auction (ERA) is examined. Drawing on the literature, a conceptual model is developed that relates procedural fairness to two key ERA outcomes: relationship quality and quality of the offering. The hypothesized relationships between procedural fairness and quality outcomes are empirically tested through a global field study with 179 procurement professionals in multinational companies, and explored through a support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 96 publications
0
10
0
1
Order By: Relevance
“…Although eight studies reported on cross‐national settings (e.g., Kumar et al, 1995; Lund et al, 2013; Muylle & Standaert, 2016; Praxmarer‐Carus et al, 2013; Scheer et al, 2003; Wagner et al, 2011), only three studies (i.e., Kumar et al, 1995; Lund et al, 2013; Scheer et al, 2003) compared results across countries and cultures. The subjective nature of the perception of inter‐organisational (in)justice (Pan et al, 2020) suggests that national cultural values can potentially exert considerable influence on how inter‐organisational (in)justice is perceived and managed in the relationship.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although eight studies reported on cross‐national settings (e.g., Kumar et al, 1995; Lund et al, 2013; Muylle & Standaert, 2016; Praxmarer‐Carus et al, 2013; Scheer et al, 2003; Wagner et al, 2011), only three studies (i.e., Kumar et al, 1995; Lund et al, 2013; Scheer et al, 2003) compared results across countries and cultures. The subjective nature of the perception of inter‐organisational (in)justice (Pan et al, 2020) suggests that national cultural values can potentially exert considerable influence on how inter‐organisational (in)justice is perceived and managed in the relationship.…”
Section: Resultsmentioning
confidence: 99%
“…An increasing body of research unveils that the perception of inter‐organisational justice can significantly contribute to the success of SCRs. It has been documented that inter‐organisational justice not only reduces conflict (Brown et al, 2006) and opportunism (Luo et al, 2015) in the relationship but also enhances relationship quality (Muylle & Standaert, 2016), commitment (Zaefarian et al, 2016), trust (Hofer et al, 2012), satisfaction (Brock et al, 2013), collaboration (Wang et al, 2014) and knowledge sharing (Liu et al, 2012). On the other hand, violation of inter‐organisational justice can be detrimental to SCRs.…”
Section: Introductionmentioning
confidence: 99%
“…The equal treatment and justification of departures from equality. Muylle and Standaert (2016) Those showing Futuregrowth and Canter's commitment to be impartial, to avoid favouritism and discrimination (such as equality, fairness and impartiality).…”
Section: Fairnessmentioning
confidence: 99%
“…Although the first-mentioned benefit, financial savings, is reflected only on the side of clients, increased transparency makes e-RA desirable for contractors as well. Muylle and Standaert [15] revealed that use of procedural fairness in e-RA is positively related to relationship quality. Financial savings can be expected if a sufficient level of competition exists in the tender [16].…”
Section: State Of the Artmentioning
confidence: 99%